Investigating Malaysian secondary school mathematics teachers` perception of National Philosophy of Education - Lessani, Abdolreza; Md Yunus, Aida Suraya; Ahmad Tarmiz, Rohani; Mahmud, Rosnaini (Canadian Center of Science and Education, 2014)
The purpose of this study is to investigate the Malaysian secondary schools mathematics teachers’ perceptions towards the National Philosophy of Education (NPE) and its applications in their teaching practices in their classes. A qualitative and case study approach was used for this study. The participants were secondary schools teachers of mathematics with at least three years of teaching experiences in eighth grade (Form 2), who were selected using the snowball sampling method. Due to the aim of this study and in order to identify the teachers’ perceptions of the national philosophy of education, interviews were conducted with seven teachers, and it was counterchecked with the documents of the Ministry of Education (MOE) in Malaysia to find out how familiar the participants were with the MOE aims and guidelines. Moreover, observations were conducted to examine teaching practices of the teachers to find out how they reflect on the guidelines of Malaysia MOE in determining their teaching practices. Analysis of the data revealed that the teachers had some knowledge of national philosophy of education in Malaysia. However, they had different perspectives of the aims and objectives of NPE so that each of them came up with her own approach. Furthermore, the teachers and MOE aims were to build up individuals who deeply believe in God and they attempted to adopt the educational syllabus of Malaysian schools to achieve the national goals toward producing the knowledgeable and competent students in Malaysia.